Amelia Jane again - Blyton, Enid. (b)
Amelia Jane is big, bad and the terror of the toy cupboard! In this book, she gives the toys some terrible scares with her mischief and gets poor Teddy to carry her home without him knowing it. Sometimes the toys get their own back ... Ages 5+.
Keywords: Amelia Jane -- Juvenile fiction. -- (Fictitious character); Amelia Jane -- (Fictitious character).